How Can Covid-19 Affected to Labor Sectors? A Critical Note - Ilham Ma'ruf Arif Legowo (Universitas Negeri Semarang, 2020)
Circular of the Minister of Manpower Number M / 3 / HK.04 / III / 2020 concerning Protection of Workers / Laborers and Business Continuity in the Prevention and Countermeasure of COVID-19, especially Part II Point 4 which reads: